(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-10-22 Abstract. This article presents the folklorist’s view of the famous story by A.P. Chekhov “I want to Sleep” (1988), reveals his biographical and folklore-ethnographic contexts, shows his connection with the social institute of nanny girls and autobiographical memoirs about this experience. Special attention is paid to the deep connection of the story with the tradition of a lullaby, common motifs and images of the author’s work and folklore songs are revealed, the so-called “mortal” lullabies – songs with a wish for the imminent death of the baby, the image of his funeral. If in the “mortal” lullabies death was replaced by sleep, then in the story “I want to sleep” the young nurse replaced the baby’s sleep with his death, setting such an incredibly high price for the opportunity to sleep soundly. It is suggested that the “mortal” lullabies, having arisen as a magical act of deceiving death, were distributed, supported among hired nannies, responding to their soulful requests. On the other hand, it is concluded that the descriptions of funerals and commemorations are smoothly logically and poetically summed up by adult threats addressed to a child, including deadly ones. A modern parody version of the “scary” lullaby is presented. The analysis once again confirms the special, implicit folklorism as a property of the poetics of the writer’s creativity. Chekhov’s story is presented as an artistic imitation of an unsuccessful lullaby. Key words: Chekhov, short story, folklore literature, babysitter girls, lullaby, death, sleep